Bridging Scales: Coupling the Galactic Nucleus to the Larger Cosmic Environment - Kung-Yi Su; Priyamvada Natarajan; Hyerin Cho; Ramesh Narayan; Philip F. Hopkins; Daniel Anglés-Alcázar; Ben S. Prather (The Astrophysical Journal Letters)
Coupling black hole (BH) feeding and feedback involves interactions across vast spatial and temporal scales that are computationally challenging to model. Tracking gas inflows and outflows from kiloparsec scales to the event horizon for non-spinning BHs in the presence of strong magnetic fields, H. Cho et al. report strong suppression of accretion on horizon scales and low (2%) feedback efficiency. In this letter, we explore the impact of these findings for the supermassive BHs M87* and Sgr A*, using high-resolution, non-cosmological, magnetohydrodynamic simulations with the FIRE-2 model. Without feedback, we find rapid BH growth due to “cooling flows,” with 2% feedback efficiency, while accretion is suppressed, the rates still remain higher than constraints from Event Horizon Telescope (EHT) data for M87* and Sgr A*. To match the EHT observations of M87*, an efficiency greater than 15% is required, suggesting the need to include enhanced feedback from BH spin. Similarly, a feedback efficiency of >15% is needed for Sgr A* to match the observationally estimated star formation rate of ≲2 M _⊙ yr ^−1 . Even with 100% feedback efficiency, the simulation-predicted Sgr A* accretion rate remains higher than EHT-inferred levels on average, while only episodically matching it, suggesting that Sgr A* is currently in a temporary quiescent phase. Bridging accretion and feedback across scales, we conclude that higher feedback efficiencies, possibly due to nonzero BH spin, are necessary to suppress “cooling flows” and match both the observed accretion and star formation rates in M87* and Sgr A*.